Combined Age with Mean Decrease Rates of Total Bilirubin and MELD Score as a Novel and Simple Clinical Predictor on 90-Day Transplant-Free Mortality in Adult Patients with Acute Liver Failure Undergoing Plasma Exchange: A Single-Center Retrospective Study - Di Jin; Kai Kang; Bing-zhu Yan; Jian-nan Zhang; Jun-bo Zheng; Zhi-hui Wang; Di Wu; Yu-jia Tang; Xin-tong Wang; Qi-qi Lai; Yang Cao; Hong-liang Wang; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background. Acute liver failure (ALF), previously known as fulminant hepatic failure, has become a common, rapidly progressive, and life-threatening catastrophic hepatic disease in intensive care unit (ICU) due to the continuous increase in drug abuse, viral infection, metabolic insult, and auto-immune cause. At present, plasma exchange (PE) is the main effective alternative treatment for ALF in ICU clinical practice, and high-volume plasma exchange (HVP) has been listed as a grade I recommendation for ALF management in the American Society for Apheresis (ASFA) guidelines. However, no existing models can provide a satisfactory performance for clinical prediction on 90-day transplant-free mortality in adult patients with ALF undergoing PE. Our study aims to identify a novel and simple clinical predictor of 90-day transplant-free mortality in adult patients with ALF undergoing PE. Methods. This retrospective study contained adult patients with ALF undergoing PE from the Medical ICU (MICU) in the Second Affiliated Hospital of Harbin Medical University between January 2017 and December 2020. Baseline and clinical data were collected and calculated on admission to ICU before PE, including gender, age, height, weight, body mass index (BMI), etiology, total bilirubin, direct bilirubin, indirect bilirubin, prothrombin activity, model for end-stage liver disease (MELD) score, and sequential organ failure assessment (SOFA) score. Enrolled adult patients with ALF undergoing PE were divided into a survival group and a death group at discharge and 90 days on account of medical records and telephone follow-up. After each PE, decreased rates of total bilirubin and MELD score and increased rates of prothrombin activity were calculated according to the clinical parameters. In clinical practice, different patients underwent different times of PE, and thus, mean decrease rates of total bilirubin and MELD score and mean increase rate of prothrombin activity were obtained for further statistical analysis. Results. A total of 73 adult patients with ALF undergoing 204 PE were included in our retrospective study, and their transplant-free mortality at discharge and 90 days was 6.85% (5/73) and 31.51% (23/73), respectively. All deaths could be attributed to ALF-induced severe and life-threatening complications or even multiple organ dysfunction syndrome (MODS). Most of the enrolled adult patients with ALF were men (76.71%, 56/73), with a median age of 48.77 years. Various hepatitis virus infections, unknown etiology, auto-immune liver disease, drug-induced liver injury, and acute pancreatitis (AP) accounted for 75.34%, 12.33%, 6.85%, 4.11%, and 1.37% of the etiologies in adult patients with ALF, respectively. Univariate analysis showed a significant difference in age, mean decrease rates of total bilirubin and MELD score mean increase rate of prothrombin activity, decrease rates of total bilirubin and MELD score, and increase rate of prothrombin activity after the first PE between the death group and survival group. Multivariate analysis showed that age and mean decrease rates of total bilirubin and MELD score were closely associated with 90-day transplant-free mortality in adult patients with ALF undergoing PE. The 90-day transplant-free mortality was 1.081, 0.908, and 0.893 times of the original value with each one-unit increase in age and mean decrease rates of total bilirubin and MELD score, respectively. The areas under the receiver operatingcharacteristic (ROC) curve of age, mean decrease rates of total bilirubin and MELD score, and the three combined were 0.689, 0.225, 0.123, and 0.912, respectively. The cut-off values of age, mean decrease rates of total bilirubin and MELD score, and the three combined were 61.50, 3.12, 1.21, and 0.33, respectively. The specificity and sensitivity of combined age with mean decrease rates of total bilirubin and MELD score for predicting 90-day transplant-free mortality in adult patients with ALF undergoing PE were 87% and 14%. Conclusion. Combined age with mean decrease rates of total bilirubin and MELD score as a novel and simple clinical predictor can accurately predict 90-day transplant-free mortality in adult patients with ALF undergoing PE, which is worthy of application and promotion in clinical practice, especially in the identification of potential transplant candidates.